I didn't want to remember memories of caring, but I can't help it": A qualitative study of the experiences of bereaved Iranian carers with elevated levels of prolonged grief symptoms. Issue 2 (7th February 2023) - Salehi, Delaram; Zarani, Fariba; Fata, Ladan; Sharbafchi, Mohammad Reza; Lobb, Elizabeth
Abstract: The lived experience of caring for people with cancer and the influence of culture on Iranian carers who have elevated levels of prolonged grief symptoms after the death has received little in-depth attention. Bereaved carers ( N = 17) were interviewed. All showed high levels of prolonged grief symptoms. Thematic analysis resulted in four overarching themes: unfamiliarity with cancer, high involvement in carer's role, lack of processing events, and emptiness. The way that carers of cancer patients understand and cope with their caring role and their dominant cultural context can make their grieving process complex.